The Phenomenon of Early Marriage in the Seginim Sub-District South Bengkulu District - Yuanta, Tia; Nopianti, Heni; Widiyarti, Diyas (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. Early marriage is a marriage event conducted by a man and a woman under the minimum age of marriage. As happened in Seginim Subdistrict, South Bengkulu Regency, the number of early marriages that occur is relatively high. This research uses a qualitative approach, described descriptively. The techniques used to collect data are non-participant observation, semi-structured interviews, and documentation studies. The data analysis technique used in this research is the Miles and Huberman data analysis model, which includes data collection, data reduction, data presentation, and conclusion drawing. The theory used to analyze the results of this study is Max Weber's social action theory. This study found several findings, namely that early marriage was caused by marriage by accident and not wanting to go to school, lack of knowledge about marriage from both adolescents and parents of adolescents who entered into early marriage, especially regarding the provisions of the minimum age of marriage and the attitude of parents of adolescents who entered into early marriage who were not too strict with their children, especially for their children who only married because they were tired of school. So, it can be concluded that the low knowledge of adolescents regarding the essence and provisions of the minimum age of marriage. Keywords: Early marriage, Phenomena, Seginim, South Bengkulu, Teenagers. Abstrak. Perkawinan dini adalah peristiwa perkawinan yang dilakukan oleh seorang pria dan wanita yang masih di bawah usia perkawinan minimal. Seperti yang terjadi di Kecamatan Seginim, Kabupaten Bengkulu Selatan, jumlah perkawinan dini yang terjadi relatif tinggi. Penelitian ini menggunakan pendekatan kualitatif yang dijelaskan secara deskriptif. Teknik yang digunakan untuk mengumpulkan data adalah observasi non-partisipan, wawancara semi-struktural, dan studi dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah model analisis data Miles dan Huberman, yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Teori yang digunakan untuk menganalisis hasil penelitian ini adalah teori tindakan sosial Max Weber. Penelitian ini menemukan beberapa temuan, yaitu bahwa perkawinan dini disebabkan oleh perkawinan yang terjadi secara tidak sengaja dan tidak ingin melanjutkan sekolah, kurangnya pengetahuan tentang perkawinan baik dari remaja maupun orang tua remaja yang melakukan perkawinan dini, khususnya terkait ketentuan usia perkawinan minimal dan sikap orang tua remaja yang melakukan perkawinan dini yang tidak terlalu tegas terhadap anak-anak mereka, terutama untuk anak-anak mereka yang hanya menikah karena merasa lelah dengan sekolah. Oleh karena itu, dapat disimpulkan bahwa rendahnya pengetahuan remaja mengenai esensi dan ketentuan usia perkawinan minimal. Kata Kunci: Perkawinan dini, Fenomena, Seginim, Bengkulu Selatan, Remaja.